Morphology of the rat knee joint after intraarticular injection of hydroxymethyl-quinoxaline dioxide - Degtiar, A.V. (Medicni Perspektivi, 2022)
Topical antiseptics are widely used in orthopedics and traumatology. However, studies highlighting the effects of antiseptics during long-term use on joint tissues are limited. In the performed work, the peculiarities of the structure of intra-articular tissues of the knee joint and muscles in rats in two series of experiments were noted: control group (saline injection into the joint) and experimental group (hydroxymethyl-quinoxaline dioxide injection into the joint) daily for 5 days. Histological methods with semi-quantitative assessment of articular cartilage and synovial membrane were used. During the first day after the drug administration, similar reactive changes to the injection of saline and hydroxymethyl-quinoxaline dioxide were observed in the joint tissues of the two groups of rats. The synovial membrane of the capsule was thickened, and synoviocytes were hypertrophied. The articular cartilage contains single cells with dense nuclei only in the superficial parts, but in general, the cytoarchitectonics of articular cartilage was preserved. In 5 days after injection, no statistically significant differences between saline and hydroxymethyl-quinoxaline dioxide were observed for the study periods. According to the studies the safety of long-term use of the drug as an antiseptic for articular tissues was confirmed.